Pollen and spores as a passive monitor of ultraviolet radiation - Fraser, Wesley T.; Lomax, Barry H.; Jardine, Phillip E.; Gosling, William D.; Sephton, Mark A. (Frontiers in Ecology and Evolution, 2014)
Sporopollenin is the primary component of the outer walls of pollen and spores. The chemical composition of sporopollenin is responsive to levels of ultraviolet (UV) radiation exposure, via a concomitant change in the concentration of phenolic compounds. This relationship offers the possibility of using fossil pollen and spore chemistry as a novel proxy for past UV flux. Phenolic compounds in sporopollenin can be quantified using Fourier Transform infrared spectroscopy. The high potential for preservation of pollen and spores in the geologic record, and the conservative nature of sporopollenin chemistry across the land plant phylogeny, means that this new proxy has the potential to reconstruct UV flux over much longer timescales than has previously been possible. This new tool has important implications for understanding the relationship between UV flux, solar insolation and climate in the past, as well as providing a possible means of assessing paleoaltitude, and ozone thickness.